Positioning Error Analysis of Ultrasonic Shear Wave Detection for Railway Vehicle Shaft - ZHOU Gang (机车电传动)
Defect positioning error of railway vehicle shaft ultrasonic wave detection was analyzed. With test comparison of the two kinds of 13mm × 13mm and 22mm × 25mm size chip shaft shear wave oblique probe, K value measured deviation was found being the chief cause of ultrasonic wave detection axle positioning error, thus, shear angle probe zero calibration and K values test method were modified to improve defect location accuracy, and 18mm × 18mm or 22mm × 25mm size chip oblique probes was recommended to use.